Escritura somática: la materialidad de la escritura en las literaturas ibéricas de la Edad Media a la temprana modernidad - Béreiziat-Lang, Stephanie; Folger, Robert; Palacios Larrosa, Miriam (The medieval and early modern Iberian world, 2020)
How is a body written, and in which ways can literary texts shed light on the tension between immediate bodily expressions and writing if medieval writing practices compete with the new technology of printing? The present volume Escritura somática: La materialidad de la escritura en las literaturas ibéricas de la Edad Media a la temprana modernidad explores the relations between corporality and writing in genres and discourses that are key for understanding the phenomenon. The Iberian perspective, including contributions on Spanish and Portuguese texts, focusses on the materiality of writing with a shared epistemic frame. Contributors are Isabel de Barros Dias, Stephanie Béreiziat-Lang, Juan Casas Rigall, Robert Folger, Juan Pablo Mauricio García Álvarez, Miguel García-Bermejo Giner, Folke Gernert, Santiago Gutiérrez García, Simon Kroll, Miriam Palacios Larrosa, Adrián J. Sáez, and Margarida Santos Alpalhão
Keywords: Aufsatzsammlung; Geschichte 1500-1680; Schreiben; Körper; Literatur; Altokzitanisch; Portugiesisch; Spanisch